Software-supported Discursive Textual Analysis: IRaMuTeQ and subcorpus analysis - Valderez Marina do Rosário Lima (2021)
Introduction: the focus of this work is the process of generating categories from the analysis of subcorpus of qualitative data that are supported in the IRaMuTeQ software. The relevance is due to the absence of subcorpus analysis in the literature, including from different areas, in the use of said software. The central theme is the nuances related to Science Clubs in basic education schools. Objective: the aim was to present subcorpus analyses in the categorization procedure that use the method of textual discursive analysis supported by the IRaMuTeQ software, with a view to understanding the generation of intermediate categories. Method: it is a qualitative approach research. The corpus and subcorpus of analysis is a dialogue about the world of Science Clubs between two researchers experienced in the subject. The analytical method adopted is the Textual discursive analysis supported by the IRaMuTeQ software. In the software, both for Corpus and subcorpus analysis, the basic analysis was the descending hierarchical classification. Results: the data analysis identified the emergence of five intermediate categories, and it is possible to identify as the main result, from subcorpus analyses, the identification of the composition of each intermediate category by another five to seven initial categories. Conclusions: the subcorpus analysis procedure is of paramount importance for the understanding of the constructions of each intermediate category emerged in the software adopted to support the method of textual discursive analysis, being configured as an advanced level, with groupings, of the initial categorization stage, not being the first movement, but still within the initial stage.